The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1074/jbc.m117.802702
|View full text |Cite
|
Sign up to set email alerts
|

A plant/fungal-type phosphoenolpyruvate carboxykinase located in the parasite mitochondrion ensures glucose-independent survival of Toxoplasma gondii

Abstract: is considered to be one of the most successful intracellular pathogens, because it can reproduce in varied nutritional milieus, encountered in diverse host cell types of essentially any warm-blooded organism. Our earlier work demonstrated that the acute (tachyzoite) stage of depends on cooperativity of glucose and glutamine catabolism to meet biosynthetic demands. Either of these two nutrients can sustain the parasite survival; however, what determines the metabolic plasticity has not yet been resolved. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
(74 reference statements)
2
26
0
Order By: Relevance
“…S4). An apparent redundancy in L-lactate transport is also in accordance with the exceptional metabolic plasticity observed in the central carbon metabolism of tachyzoites (16,18,19). FNTs discriminate between different monocarboxylate substrates by size selection in the ⌽/K filter region (7).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…S4). An apparent redundancy in L-lactate transport is also in accordance with the exceptional metabolic plasticity observed in the central carbon metabolism of tachyzoites (16,18,19). FNTs discriminate between different monocarboxylate substrates by size selection in the ⌽/K filter region (7).…”
Section: Discussionsupporting
confidence: 66%
“…Earlier work has demonstrated the expression of high-affinity sugar permeases in both parasites (12,13), which allow import of glucose (besides other hexoses) and its subsequent catabolism through glycolysis (14 -16). Surprisingly, glucose import is essential for asexual growth of the acute (termed merozoite) stage in Plasmodium (17,18) but dispensable for the acute (termed tachyzoite) stage of T. gondii (16,18,19). Previous works by several groups have also characterized lactate dehydrogenases in the two parasites (20,21), which are meant to enable recycling of NADH ϩ to NAD ϩ and thus ensure a continued glycolysis.…”
mentioning
confidence: 99%
“…Several bacterial species are known to degrade taurine via a pathway that results in the nitrogen being incorporated into alanine and other amino acids [24,25]. However, no 15 N was detected in any intracellular metabolite except taurine, and taurine levels did not decrease as previously observed. This…”
Section: Taurine Releasesupporting
confidence: 63%
“…This glutamine to glucose pathway relies on a gluconeogenic enzyme fructose bisphosphatase 2, which was found to be constitutively expressed and essential to growth [7]. Similarly, T. gondii catabolism of glutamine to fuel gluconeogenesis is reliant on a mitochondrial phosphoenolpyruvate carboxykinase enzyme, which is thought to play a key regulatory role in T. gondii carbon metabolism [15]. The metabolic flexibility of T. gondii is remarkable, recent work has even shown that growth will occur in environments completely lacking glucose and glutamine [16].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic-tagging of TgATPase P -GC and TgPKG--Sequences of TgATPase P -GC (TGGT1_254370) and TgPKG (TGGT1_311360) genes were obtained from the parasite genome database (ToxoDB) (Gajria, Bahl, Brestelli, Dommer, Fischer, Gao, Heiges, Iodice, Kissinger, Mackey, Pinney, Roos, Stoeckert, Wang and Brunk 2008). The expression and subcellular localization of TgATPase P -GC and TgPKG were determined by 3'-insertional tagging (3'IT) of corresponding genes with an epitope, essentially as reported before (Nitzsche et al 2017). To achieve this, the 3' end of the gene (1-1.5 kb 3'-crossover sequence or COS) was amplified from gDNA of the RHΔku80-hxgprtstrain using Q5 TM High-Fidelity DNA Polymerase (Bio-Rad Laboratories, Germany) (see Table S1 for primers).…”
Section: Methodsmentioning
confidence: 99%